Effects of Shiitake mushroom (Lentinus edodes) supplementation into quail diets on performance, blood serum parameters and intestine microbial populations : Effects of Shiitake Mushroom (Lentinus edodes) Supplementations into Quail Diets - Ay, C; Ülger, İ and Kaliber, M and Hızlısoy, H and Ayasan, T (Journal of the Hellenic Veterinary Medical Society, 2023)
This study was conducted to investigate the effects of shiitake mushroom (Lentinus edodes) (SM) supplementations into quail diets on live weight (LW), live weight gain (LWG), feed consumption (FC), feed conversion ratio (FCR), blood serum biochemical parameters (total cholesterol, total protein, triglyceride, glucose) and intestine bacteria populations. A total of 120 Japanese quail (Coturnix coturnix Japonica) were used in present experiments. Quail were separated into 4 groups (control and 3 treatment groups). Control group was fed with a basic ration and treatments groups were fed with 0.5, 1 and 2% shiitake mushroom-supplemented diets. Shiitake mushroom supplementations significantly influenced live weights (P<0.05). Differences in live weight gains, feed consumptions, feed conversion ratios, blood serum parameters and intestine bacteria populations of the treatment groups were not found to be significant (P>0.05). SM supplementations influenced live weight gains and feed conversion ratios in the 4th week of the experiments (P>0.05). SM supplementations also influenced blood serum glucose levels (P<0.05).